2015
DOI: 10.1902/jop.2015.140434
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Leptin and Visfatin in Gingival Tissues of Chronic Periodontitis With and Without Type 2 Diabetes Mellitus: A Study Using Enzyme‐Linked Immunosorbent Assay and Real‐Time Polymerase Chain Reaction

Abstract: Expression of leptin and visfatin in the gingival tissues suggests a possible role for these adipokines in the pathogenesis of CP and T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 55 publications
1
18
0
1
Order By: Relevance
“…In this study, it was found that saliva visfatin levels were higher in patients with periodontitis than in the healthy individuals, which decreased at 3 months and remained low until 6 months. In several studies, high levels of visfatin have been reported in saliva, GCF, and periodontal tissue in periodontitis 6,7,41‐43 . In contrast, visfatin GCF and saliva levels have been reported to decrease after NSPT 15–18 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that saliva visfatin levels were higher in patients with periodontitis than in the healthy individuals, which decreased at 3 months and remained low until 6 months. In several studies, high levels of visfatin have been reported in saliva, GCF, and periodontal tissue in periodontitis 6,7,41‐43 . In contrast, visfatin GCF and saliva levels have been reported to decrease after NSPT 15–18 .…”
Section: Discussionmentioning
confidence: 99%
“…Adipokines are molecules with a protein structure, involved in various systemic events such as the regulation of glucose released from the adipose tissue, homeostasis, inflammation, and healing 34 . They play an important role in many diseases, especially diabetes and obesity 14 , 15 , 34 . The increased expression of some adipokines is known to be associated with BMI and age 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with periodontitis, in the presence of systemic inflammatory diseases and conditions such as rheumatoid arthritis, diabetes, and obesity, inflammatory response of the tissue may vary, and the periodontal breakdown can be more prevalent 12 . Although the underlying mechanisms have not been determined precisely, it has been speculated that adipokines might represent an important pathophysiologic link between periodontitis and systemic diseases 13–15 . Recently, some adipokines are reported to play a role in immune regulation and the inflammatory process 16 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Adipokines are thought to act via their impact on insulin sensitivity, which is why fluctuating levels of these hormones are linked to T2DM (29). Recently, Ogawa et 0.000* 0.000* 0.000* 0.000* 0.000* 0.000* 0.000* 0.000* 0.000* CTRL, systemically and periodontally healthy control group; DM-CTRL, type 2 diabetes with periodontally healthy group; CP, chronic periodontitis without type 2 diabetes group; DM-CP, chronic periodontitis with type 2 diabetes group; TNF-α, tumor necrosis factor-alpha; GI, gingival index; CAL, clinical attachment level; HbA1c, glycated haemoglobin A1c.…”
Section: Discussionmentioning
confidence: 99%